Pelatihan Implementasi Pembelajaran Berorientasi pada Keterampilan Berpikir Tingkat Tinggi bagi Guru-Guru SMP Negeri 7 Depok, Jawa Barat - Imam Safi’i; Wini Tarmini; Sobri Sobri (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING ON IMPLEMENTATION OF LEARNING ORIENTED ON HIGHER ORDER THINKING SKILL FOR TEACHERS OF SMP NEGERI 7 DEPOK, WEST JAVA. Learning oriented towards higher-order thinking skills is a learning activity that aims to improve students' ability to think critically, creatively, analytically, and logically. This Community Service activity aims to improve the competence of teachers of SMP Negeri 7 Depok, West Java in implementing learning that is oriented to higher-order thinking skills. The method used in this training is a workshop that refers to the genre pedagogy training model, which starts with conditioning, modeling, designing learning together, and finishing learning independently. After participating in training activities, teachers can design and implement learning activities oriented to high-level skills well. The results of the training can be used as a model for better learning and are relevant to the demands of the 2013 Curriculum.